2012
DOI: 10.1111/j.1741-2358.2011.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of soft tissue oral lesion in elderly and its relations with deleterious habits

Abstract: Prevalence of soft tissue oral lesion in elderly and its relations with deleterious habitsIntroduction: With ageing, the oral mucosa becomes more susceptible to external stimuli. Objective: To investigate the prevalence of soft tissue oral lesion in elderly and its relations with deleterious habits. Materials and methods: It was a quantitative research conducted at the dental clinic of UNIFOR, Fortaleza-CE, in the period from 1998 to 2006. The sample consisted of all 756 records of the elderly, and the data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The present authors found a decrease in the incidence of OMLs with advancing age, which is a finding consistent with other studies. [ 11 20 ] However, this result differs from the ones reported by Jainkittivong et al . [ 5 ] and Ferreira et al .…”
Section: Discussionmentioning
confidence: 64%
“…The present authors found a decrease in the incidence of OMLs with advancing age, which is a finding consistent with other studies. [ 11 20 ] However, this result differs from the ones reported by Jainkittivong et al . [ 5 ] and Ferreira et al .…”
Section: Discussionmentioning
confidence: 64%
“…Smoking tobacco is the most responsible factor for the development of intraoral white lesions. These lesions are more frequent in tobacco chewers and pipe smokers than in those who smoke cigarettes, and the amount of daily consumption and period of addiction are also important 14. However, leukoplakia (14%) was the most common mucosal condition in another study 13.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, 3 of the 258 smokers (1.1%) had SCC. Thus, implementation of regular dental services and care and health education is essential in high-risk patients 14. In one study, the most common OMLs were fissured tongue, coated tongue, aphthae, linea alba, glossitis, leukoplakia, candidiasis, and macroglossia 12.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations